Factors affecting growth of the spiny lobsters Panulirus gracilis and Panulirus inflatus (Decapoda: Palinuridae) in Guerrero, México - Briones-Fourzán, Patricia (2003)
The effects of sex, injuries, season and site on the growth of the spiny lobsters Panulirus gracilis, and P. inflatus, were studied through mark-recapture techniques in two sites with different ecological characteristics on the coast of Guerrero, México. Panulirus gracilis occurred in both sites, whereas P. inflatus occurred only in one site. All recaptured individuals were adults. Both species had similar intermolt periods, but P. gracilis had significantly higher growth rates (mm carapace length week-1) than P. inflatus as a result of a larger molt increment. Growth rates of males were higher than those of females in both species owing to larger molt increments and shorter intermolt periods in males. Injuries had no effect on growth rates in either species. Individuals of P. gracilis grew faster in site 1 than in site 2. Therefore, the effect of season on growth of P. gracilis was analyzed separately in each site. In site 2, growth rates of P. gracilis were similar in summer and in winter, whereas in site 1 both species had higher growth rates in winter than in summer. This could be due to spatial differences in processes related to changes in population density and food resources, which were documented in previous works. The overall results show that P. gracilis grows faster than P. inflatus, and that growth rates of both species are highly variable and are affected by environmental factors such as site and season, which should be taken into account when attempting to produce population growth curves for each species.